Exploring the Tshwane –Kungwini municipal amalgamation process - Kabale, Unathi (My University, 2020)
A significant debate on municipal amalgamations involves whether big consolidated governments are better than smaller ones. In this debate, some argue that consolidation is a useful instrument for achieving economies of scale and distributing resources equitably. The debate mainly captures two contrasting views. One side views big councils to be more capable of distributing services at economies of scale more equitably and responsively. In contrast, it is believed that smaller councils are more responsive to local issues and are more competitive with their counterpart municipalities. This debate mainly consists of arguments on efficiency, equity and democracy. This report adds to the already existing work on amalgamations by exploring them in a post-apartheid South African context. It aims to understand why amalgamations are needed, how they work and whether they are useful tools for addressing local government problems. The report examines the amalgamation issue in the case of the 2011 City of Tshwane amalgamation with the former Kungwini local municipality. The methods for carrying out this report include the review of international and South African debates on amalgamations. The report also uses secondary data sources such as national and local government documents. In addition, it draws from key informant interviews conducted with informants from the Municipal Demarcation Board, national and local government. The report finds that the amalgamation occurred as a result of a pursuit towards city regions in Gauteng and the removal of district municipalities. Furthermore, local government problems were identified in Kungwini, which further influenced the amalgamation to be conducted. The report finds that the benefits of this amalgamation were partial in that, some problems were addressed, however, others related to service delivery still remain. The problems addressed include poor debt and revenue collection, inadequate standard of policies, financial mismanagement, budget deficits and a lack of operational systems such as geographic information systems. The incorporation allows Tshwane to eliminate these problems by offering better services and having stronger systems put in place. One major shortcoming of this amalgamation however, is the high associated costs for the merger which involves the absorption of debts from Kungwini and along with its service backlogs
A research report submitted to the School of Architecture and Planning, University of the Witwatersrand, in partial completion of the requirements of the Master’s degree in Development Planning, 2020